Nepal’s Trade Flows: Evidence from Gravity Model - Thapa, Surya Bahadur (NRB Economic Review, 2012)
This study is carried out to estimate the trade potentiality of Nepal using gravity model. The gravity model simply explains that the volume of trade between pairs of countries is a positive function of the size of two countries and negative function of the distance between them. The study has used coefficients of the model to predict Nepal’s foreign trade for the year 2009. The trade potentiality is calculated with the help of the ratio of predicted trade to actual trade. The result is fluctuating: some countries crossed the limits whereas some countries are still below the potential trade. The study has used gravity model to evaluate the determinants of foreign trade of Nepal using secondary data including 19 major trade partners. The estimated result of Nepal’s trade potentiality shows that Nepal has exceeded trade potentiality with her 10 trading partners, including giant neighbors India and China, and there remains trade potentiality with 9 trade partners including another neighbor Bangladesh.